Development of Carbon Monoxide Gas Detection and Monitoring System in Vehicle Cabin with Auto Ventilation and Auto Engine Switch Off - SAIFUL ANUAR, MUHAMMAD AFIF HILMI BIN; ISHAK, DR IZUAN AMIN BIN; Mohammad Arafat (Progress in Engineering Application and Technology, 2024)
The development of an effective carbon monoxide (CO) detection system in vehicle cabins is crucial to ensure passenger safety. This project aims to design and implement a system that not only monitors CO levels but also takes automated actions to mitigate potential hazards. Elevated CO levels in enclosed vehicle cabins can lead to serious health issues or fatalities, and existing solutions either focus on monitoring or providing alarms without integrating comprehensive automated responses. This project addresses the gap by offering an all-in-one solution that ensures immediate action when hazardous conditions are detected. The objective is to develop a reliable CO detection system for vehicle cabins that alerts occupants and initiates automated safety measures to reduce CO exposure. Using an Arduino Uno, MQ-9 gas sensor, LCD display, and dual-channel relay, the system is designed to monitor CO levels continuously and activate the relay to cut off the engine and roll down the windows if CO concentrations exceed 70 ppm for more than 30 seconds. Rigorous testing was conducted to ensure the system's responsiveness and reliability under various scenarios, refining the algorithm to minimize false positives and negatives. The results indicate that the system effectively detects CO levels above the threshold and initiates the safety measures within the specified time frame, with the LCD display providing clear real-time feedback. In conclusion, the CO detection system with automated ventilation and engine switch-off functions significantly improves vehicular safety by reducing the risks associated with CO exposure. It is recommended that future studies explore integrating additional safety features, such as emergency notification modules and enhancements in sensor accuracy and response times, to further enhance the system's effectiveness and reliability.